Formulation and Physical Stability Test of Body Scrub Cream with Mangosteen Peel Extract (Garcinia Mangostana L) - Yumiyati; Ratih Nurwanti; Sarni (Yayasan Cipta Anak Bangsa (YCAB) Publisher, 2026)
Background: Mangosteen (Garcinia mangostana L.) is a plant known for its various beneficial properties, particularly in its thick skin, which contains xanthone compounds. These compounds have antioxidant properties that are beneficial for the skin. The use of mangosteen skin extract as a key ingredient in body scrub creams has gained attention due to its potential skin benefits. Objectives: This study aimed to develop a body scrub cream formulation using mangosteen skin extract (Garcinia mangostana L.), assess the physical stability of the cream, and determine the most optimal formulation for its preparation. Methods: This study employed a laboratory experimental design, utilizing a maceration extraction method with 96% ethanol as the solvent to extract mangosteen skin compounds. Three different body scrub cream formulations were prepared with varying concentrations of mangosteen skin extract: Formula 1 (5%), Formula 2 (10%), and Formula 3 (15%). The physical stability and effectiveness of each formulation were tested through organoleptic evaluation, homogeneity, pH, adhesion, spreadability, and cream stability tests. Results: All three body scrub cream formulas were successfully formulated with mangosteen skin extract. However, none of the formulations met the optimal criteria. While all formulas passed the physical stability tests, including organoleptic evaluation, homogeneity, pH, adhesion, and cream consistency, none of the formulas passed the spreadability test. Conclusion: Although the body scrub creams demonstrated acceptable physical characteristics, the spreadability aspect requires further improvement to meet the expected standards for an optimal product. The results indicate the potential of mangosteen skin extract in body scrub formulations, but refinements are necessary to enhance the overall quality. Keywords: Body Scrub Cream, Mangosteen Peel, Phycal Stability Test